Chemical modifications of poly(3-hydroxyalkanoates). Issue 2 (20th June 2015) - Bhatt, Rachana; Jaffe, Michael
Abstract : Microbially produced polyhydroxyalkanoates (PHAs) are fully biodegradable and biocompatible biopolyesters. Several different varieties of PHAs are directly produced by microbial fermentation. PHAs with tailor-made compositions can be synthesized by choosing an appropriate strain, carbon source, and suitable cultivation condition. However, some thermomechanical properties need to be improved for increasing the application range of these PHAs, and this can be achieved by chemical modifications of microbially synthesized PHAs. To date, several chemical modifications of PHAs have been reported. This literature survey summarizes such chemical modifications of polyhydroxybutyrate, poly (3-hydroxybutyrate-co-3-hydroxyvalerate), poly (hydroxybutyrate-co-hydroxyhexanoate), and polyhydroxyoctanoate.